2018
DOI: 10.1002/aoc.4762
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Copper (II) complex based chemical probes for DNA targeting: Cytotoxic activity under visible light

Abstract: Among the bio‐metals, copper derivatives of O, N, S donor salicylaldehyde thiosemicarbazones have been obtained large interest due to their potential biological applications. Multisubstituted thiosemicarbazone ligand HL derived, new ternary Cu (II) complexes of [Cu(L)(bpy)] (1) and [Cu(L)(phen)] (2) (where, bpy is 2,2′‐bipyridine and phen is 1,10‐phenanthroline) have been synthesized and characterized using different physico‐chemical techniques. Complexes 1 and 2 are structurally characterized by single crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…It is important to note here that the results observed for 1 may be compared to many other reported DNA-binding copper complexes. 55 61 For example, the synthesized tyrosine Schiff base copper complexes by Reddy and Shilpa 55 showed good binding propensity for CT-DNA (3.01–3.47 × 10 4 M –1 ) and exhibited high nuclease activity as evident from the high hydrolytic DNA-cleavage rate constant (2.80–2.11 h –1 ) that amounts to a significant rate enhancement (0.5 to 0.7 × 10 8 fold) in comparison to non-catalyzed DNA hydrolysis. Yu et al 56 have reported four Cu(II) complexes of a reduced Schiff base ligand having diamine co-ligands that bind to DNA by intercalative mode and effectively induced apoptosis in cancer cells (A549, BGC823, and SGC7901), which was accompanied with increase in p53 and Bax and decrease in bcl2 expression.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note here that the results observed for 1 may be compared to many other reported DNA-binding copper complexes. 55 61 For example, the synthesized tyrosine Schiff base copper complexes by Reddy and Shilpa 55 showed good binding propensity for CT-DNA (3.01–3.47 × 10 4 M –1 ) and exhibited high nuclease activity as evident from the high hydrolytic DNA-cleavage rate constant (2.80–2.11 h –1 ) that amounts to a significant rate enhancement (0.5 to 0.7 × 10 8 fold) in comparison to non-catalyzed DNA hydrolysis. Yu et al 56 have reported four Cu(II) complexes of a reduced Schiff base ligand having diamine co-ligands that bind to DNA by intercalative mode and effectively induced apoptosis in cancer cells (A549, BGC823, and SGC7901), which was accompanied with increase in p53 and Bax and decrease in bcl2 expression.…”
Section: Resultsmentioning
confidence: 99%
“…This provides evidence for the coordination of thiolato sulfur through iminolization after deprotonation. [ 28 ]…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, it is also involved in a variety of metabolic pathways, such as mitochondrial respiration, free radical scavenging and iron absorption [20,21] . Its toxicity is based on the direct production of reactive oxygen species (ROS) that cleave DNA and RNA, and its distribution and homeostasis can be highly regulated [22,23] . Studies suggest that copper is an essential cofactor for tumor angiogenesis, because most tumor growth and metastasis depend on angiogenesis, and angiogenesis requires a specific amount of copper [24–26] .…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] Its toxicity is based on the direct production of reactive oxygen species (ROS) that cleave DNA and RNA, and its distribution and homeostasis can be highly regulated. [22,23] Studies suggest that copper is an essential cofactor for tumor angiogenesis, because most tumor growth and metastasis depend on angiogenesis, and angiogenesis requires a specific amount of copper. [24][25][26] Cobalt usually exists in the form of Co 2 + or Co 3 + , which can regulate the redox potential between normoxic and hypoxic tissues, and is the only d 7 ion.…”
Section: Introductionmentioning
confidence: 99%